Characterization of Pseudomonas fluorescens polyhydroxyalkanoate produced from molasses as a carbon source - Yusuf Hendrawan; Dikianur Alvianto; Sumardi Hadi Sumarlan; Yusuf Wibisono (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2020)
Polyhydroxyalkanoate (PHA) is a biopolymer produced by various types of bacteria under conditions of unbalanced growth. One of the bacteria generating PHA is Pseudomonas fluorescens with a carbon source in the form of molasses. This study aimed to determine the effect of molasses concentration and incubation period on biomass and PHA characteristics. This study utilised two factors, such as molasses concentration of 40, 60, 80 g/L, and incubation period for 3, 5, 7 days. The research result indicated the highest biomass yield was obtained from the treatment of 40 g/L molasses concentration and in 7-day incubation period, with dry cell weight values of 1,955 g/L, PHA weight of 0.756 g/L, dry cell yield of 2.036%, and PHA yield of 39.06%, respectively. The visual characteristics of PHA samples were indicated with brownish and granular state, while the melting point and functional groups were identical to pure polyhydroxybutyrate (PHB). The characteristics of the PHB structure obtained from Fourier Transform Infrared Spectroscopy (FTIR) analysis, depicting: C = O esters, CH3, CH2, -C-O-, -C-O-C Polymers, and C-C. The melting point of PHA samples,using Differential Scanning Calorimetry (DSC) analysis, was 166.4 oC and an enthalpy of -13.885 J/g with 9.5% degree of crystallisation.